Age and Sex‐Related Differences in Neuroprotective Effects of Cardiovascular Endurance on Cortical Thickness and Brain Volume in Adults Across Age - Junyeon Won; Marissa Gogniat; J. Carson Smith (Brain and Behavior)
ABSTRACT Background Higher cardiorespiratory fitness and cardiovascular endurance (CE) have been shown to be neuroprotective in older adulthood, but the mechanisms underlying this neuroprotection across the adult lifespan are poorly understood. The current study sought to examine the neuroprotective effects of CRF on gray matter (GM) and white matter (WM) volumes, and mean cortical thickness (MCT), using a large sample across the adult lifespan. We also examined sex differences in these relationships. Methods This cross‐sectional study included data from 1691 adults across the adult lifespan (22–100 years) from the Human Connectome Project Young Adults and Aging data. 2‐minute walk test performance was used as a proxy of CE. Structural MRI was used to assess total GM volume, WM volume, and MCT. Linear regression models were used to examine the interaction between age and CE on total GM volume, WM volume, and MCT after adjusting for sex, years of education, body mass index, systolic blood pressure, gait speed, and total intracranial volume. Whole‐brain surface‐based analysis was also performed to investigate regional effects. Finally, interactions between age, sex, and CE were examined to test sex differences. p < 0.05, two‐sided test, was designed as statistically significant. Results With greater CE, the associations between greater age and lower total and regional GM and WM volumes and MCT were attenuated in whole sample. In men, age was associated with lower total GM volume and MCT regardless of CE level. In women, attenuated negative associations between age and total GM volume and MCT were found in those with high CE. Conclusion Greater CE over the adult lifespan is associated with preservation of cortical thickness and brain volume, particularly in women.